Escherichia coli adapts metabolically to 6- and 7-fluoroindole, enabling proteome-wide fluorotryptophan substitution - Treiber-Kleinke, Christin; Berger, Allison Ann; Adrian, Lorenz; Budisa, Nediljko; Koksch, Beate (Frontiers in Synthetic Biology, 2024)
Nature has scarcely evolved a biochemistry around fluorine. However, modern science has shown that fluorinated organic molecules are suitable building blocks for biopolymers, from peptides and proteins up to entire organisms. Here, we conducted adaptive laboratory evolution (ALE) experiments to introduce organofluorine into living microorganisms. By cultivating Escherichia coli with fluorinated indole analogs, we successfully evolved microbial cells capable of utilizing either 6-fluoroindole or 7-fluoroindole for growth. Our improved ALE protocols enabled us to overcome previous challenges and adaptation was achieved, enabling a former growth inhibiting unnatural molecule to become a substrate for the cell’s protein synthesis machinery to the extent that the entire proteome underwent Trp to F-Trp substitution. In the ALE experiments, we supplied fluoroindoles to Trp-auxotrophic E. coli bacteria, exerting strong selective pressure that led to microbial adaptation. Within the cells, these indoles were converted into the corresponding amino acids (6- and 7-fluorotryptophan) and globally incorporated into the proteome at tryptophan sites. This study is a first step and establishes a strong foundation for further exploration of the mechanisms underlying fluorine-based life and how a former antimetabolite can become a vital nutrient.